2014
DOI: 10.1080/00015458.2014.11681006
|View full text |Cite
|
Sign up to set email alerts
|

Custom-Made Fenestrated Stent Grafts to Preserve Accessory Renal Arteries in Patients with Abdominal Aortic Aneurysms

Abstract: Accessory renal arteries are common and may contribute significantly to renal perfusion. With the current endovascular design and technology, it is possible to preserve accessory renal arteries during endovascular aneurysm repair (EVAR). We report two patients with custom-made EVAR devices to preserve accessory renal arteries with good mid- and long-term clinical and radiological results. Conventional EVAR would have occluded their origins. As a result of customized fenestrations in commercially available sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Chimney grafts as well as commercially or homemade fenestrated endografts have been designed and used in this setting. 6,8 10 Based on ARA configuration, patients’ clinical and anatomic characteristics, as well as technical considerations, we propose a treatment algorithm that may help surgeons to choose the most appropriate approach to treat AAA with ARA arising from the aneurysmal sac or neck (Figure 2).
Figure 2. Proposed treatment algorithm of abdominal aortic aneurysm with accessory renal arteries arising from the aneurysmal sac or neck.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimney grafts as well as commercially or homemade fenestrated endografts have been designed and used in this setting. 6,8 10 Based on ARA configuration, patients’ clinical and anatomic characteristics, as well as technical considerations, we propose a treatment algorithm that may help surgeons to choose the most appropriate approach to treat AAA with ARA arising from the aneurysmal sac or neck (Figure 2).
Figure 2. Proposed treatment algorithm of abdominal aortic aneurysm with accessory renal arteries arising from the aneurysmal sac or neck.
…”
Section: Discussionmentioning
confidence: 99%
“…5 Several endovascular procedures have been developed and can be proposed to spare the ARA, including the use of fenestrated or chimney endografts. 6 10 However, there is currently only low-quality evidence to support the strategy to cover or to preserve the ARA and the choice relies on the balance between risks and benefits for the patients. 5 A better understanding of the impact of ARA coverage on postoperative outcome may help surgeons to choose the most appropriate approach and minimize postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to a standard implant, a custom-made one is more likely to yield superior functional and esthetic outcomes (148, 149). Typical 3D printing materials can be sterilized using chemicals, such as Food and Drug Administration approved glutaraldehyde protocols (71), steam (20), and gas (150) for intraoperative handling.…”
Section: D Printing In Plastic and Reconstructive Surgerymentioning
confidence: 99%
“…Preservation of flow in relevant ARAs during EVAR is in agreement with the statement of the National Kidney Foundation, which defined CKD on the basis of established kidney damage caused by ischemia/infarction of the parenchyma independent of the changes in creatinine or GFR values. 5 Recently, Chan et al 7 reported on the use of custom-made fenestrated stent-grafts in 2 cases to preserve ARAs during EVAR. However, fenestrated technology requires advanced endovascular skills, complex sizing, and is not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, individuals with coverage of clinically relevant ARAs as defined above should be considered CKD patients, independent on the changes in serum creatinine or GFR values. 5 The current literature provides scant information, mainly case reports, 6,7 about endovascular techniques to preserve the flow to relevant ARAs during EVAR. The article presents a series of AAA patients with coexistent relevant ARAs that were treated by standard EVAR and placement of covered stents in the ARAs.…”
Section: Introductionmentioning
confidence: 99%